Abdominal Versus Laparoscopic Sacrocolpopexy: A Systematic Review and Meta-analysis. Issue 7 (July 2016) - Campbell, Patrick; Cloney, Louise; Jha, Swati
Abstract : Sacrocolpopexy (SC) is considered the criterion-standard treatment for management of vaginal vault prolapse (VVP), and laparoscopic SC (LSC) has become a popular alternative to the abdominal approach. However, there are limited definitive data comparing the 2 procedures. The aim of this meta-analysis is to compare the abdominal sacrocolpopexy (ASC) with the LSC for the management of VVP. Electronic searches of MEDLINE, EMBASE, PubMed, Cochrane Register of Controlled Trials, Cochrane Database of Systematic Reviews, CINAHL, and Google scholar were performed. A systematic review and meta-analysis of studies comparing ASC and LSC for the management of VVP were performed. Seven studies were included with a total of 1461 patients: 589 in the LSC group and 872 in the ASC group. The conversion rate for LSC to ASC was 3% (17 cases). One LSC and 1 ASC were each converted to vaginal procedures. The operative time was significantly greater with LSC (mean difference, 25 minutes; 95% confidence interval [CI], 5.43–45.07 minutes); however, ASC had significantly greater intraoperative blood loss (mean difference, 107 mL; 95% CI, −139.59 to −73.73 mL), longer hospital stay (mean difference, 1.71 days; 95% CI, −2.21 to −1.22 days), and increased risk of postoperative ileus/small bowel obstruction (odds ratio, 2.88; 95% CI, 1.31–6.33). There was no significant difference in rate of bladder injury, bowel injury, mesh exposure, or repeat prolapse surgery. Laparoscopic SC takes longer but is associated with less intraoperative blood loss, shorter hospital stay, and reduced postoperative ileus/small bowel obstruction and hence is a suitable alternative to the abdominal technique. Target Audience: Obstetricians and gynecologists, family physicians Learning Objectives: After completing this activity, the learner should be better able to (1) Understand The International Continence Society definition of vaginal vault prolapse, (2) Recognize the management options for vaginal vault prolapse, and (3) Differentiate the benefits of laparoscopic sacrocolpopexy over abdominal sacrocolpopexy.